Influence of Cultural and Historical Context on the Moral Competence in Modern Society (in Terms of Georgia and Russia) - Kaznina, Eka (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
The break-up of the Soviet Union in 1991 sharply cast the relationships between the Republics of post-Soviet space and Russia back, mutual trust was lost, economic and cultural interaction was practically stopped. The global changes of the 1990s in the field of political order, social and economic lifestyle in the countries of the former socialist camp brought up to severe demographic situation (depopulation), impoverishment of its significant part, criminalization of society and, what is quite important, to negative changes in consciousness and behavior of its population, including deformation of ethical code of personality, for long time fixing the acute social-cultural situation. A. Zhuravlev & A. Yurevich call that the moral collapse. It is worth mentioning that the economic crisis of the 90s in Georgia was considerably more serious than in Russia. Attempt to teach norms of “new” morale were done by M. Saakashvili (2009–2013), who declared that during 20 years he would be able to change the mentality of Georgians – rejection of the Russian culture and language up to prohibition and adherence to anti-Russian policy at a level of the State. The author reports on that project and she intends to find the difference of how moral competence is understood by the generation which was formed in 1990s and the generation formed under the Soviet Union.
Keywords: moral competence; religiousness; properties and states of conscience; Georgia; Russia